Sistem Informasi Pemesanan pada PT. Ivomas Tunggal Lestari Ujung Tanjung Workshop Berbasis Website - Br Nadapdap, Askeline Ruthkenera; Siringoringo, Rimbun; Harianja, Eva Julia G. (Universitas Methodist Indonesia, 2024)
Over time, information systems have become a supporting tool in carrying out daily activities in the company. Examples such as masking sales reports at PT. Ivomas Tunggal Lestari. This company is an internal company, where all its activities are only carried out by a subsidiary of PT. Ivomas Tunggal Lestari. This website based sales information system aims to help employees without having to look for files that have been scattered everywhere. This system is based on qualitative methods and implemented using PHP and Mysql. The final result obtained is a website-based sales information system used by PT. Ivomas Tunggal Lestari. This system is able to provide reports on every sales transaction.